Eine agentenbasierte Architektur für Programmierung mit gesprochener Sprache - Weigelt, Sebastian (KIT Scientific Publishing, 2022)
The system described in this work, called ProNat, makes end-user programming with spoken language possible. It enables non-experts to describe programs for different target systems and to extend their functionality using everyday language. ProNat is based on PARSE, a specially designed agent-based framework architecture. In three independent studies, ProNat has proven to be principally capable of synthesizing programs from spoken utterances.